Ventricular conduction abnormalities as predictors of long‐term survival in acute de novo and decompensated chronic heart failure. (30th October 2015) - Tolppanen, Heli; Siirila‐Waris, Krista; Harjola, Veli‐Pekka; Marono, David; Parenica, Jiri; Kreutzinger, Philipp; Nieminen, Tuomo; Pavlusova, Marie; Tarvasmaki, Tuukka; Twerenbold, Raphael; Tolonen, Jukka; Miklik, Roman; et al.
Abstract: Aims: Data on the prognostic role of left and right bundle branch blocks (LBBB and RBBB), and nonspecific intraventricular conduction delay (IVCD; QRS ≥ 110 ms, no BBB) in acute heart failure (AHF) are controversial. Our aim was to investigate electrocardiographic predictors of long‐term survival in patients with de novo AHF and acutely decompensated chronic heart failure (ADCHF). Methods and Results: We analysed the admission electrocardiogram of 982 patients from a multicenter European cohort of AHF with 3.9 years' mean follow‐up. Half (51.5%, n = 506) of the patients had de novo AHF. LBBB, and IVCD were more common in ADCHF than in de novo AHF: 17.2% vs. 8.7% ( P < 0.001) and 20.6% vs. 13.2% ( P = 0.001), respectively, and RBBB was almost equally common (6.9% and 8.1%; P = 0.5), respectively. Mortality during the follow‐up was higher in patients with RBBB (85.4%) and IVCD (73.7%) compared with patients with normal ventricular conduction (57.0%); P < 0.001 for both. The impact of RBBB on prognosis was prominent in de novo AHF (adjusted HR 1.93, 1.03–3.60; P = 0.04), and IVCD independently predicted death in ADCHF (adjusted HR 1.79, 1.28–2.52; P = 0.001). Both findings were pronounced in patients with reduced ejection fraction. LBBB showed no association with increased mortality in either of the subgroups. The main results were confirmed in a validation cohort of 1511 AHF patients with 5.9 years' mean follow‐up. Conclusions: Conduction abnormalities predict long‐term survival differently in de novo AHF and ADCHF. RBBB predicts mortality in de novo AHF, and IVCD in ADCHF. LBBB has no additive predictive value in AHF requiring hospitalization.